Introduction: Narrative figuralism and epistemic responsibility in historical controversies - Tozzi, María Verónica (2013)
The study on the status of narrative in structuring the past has been a central topic in the so-called New Philosophy of History. If we were to summarize in a few sentences the gallons of ink spent on it, we could say that “narrative is not an empty form to fill in with any external and independent content. Narrative is the content of the form”.